2012
DOI: 10.54302/mausam.v63i1.1446
|View full text |Cite
|
Sign up to set email alerts
|

A satellite based study of pre-monsoon thunderstorms (Nor’westers) over eastern India and their organization into mesoscale convective complexes

Abstract: Nor’wester studies have a long history of climatological, synoptic and radar observations. These studies have been briefly mentioned and the field programs for the study of Nor’westers implemented in India Meteorological Department (IMD) from 1931-1941 have been touched upon. Indian atmospheric science community organized a multi-year STORM program during 2007-2010 to understand the formation of these severe local storms and also understand their dynamics through modeling. An attempt is made to use INSAT Infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…During premonsoon, the eastern parts of India (Gangetic West Bengal, Assam, Odisha, Bihar, and Jharkhand) experience severe TS, locally known as Nor'westers or Kal-Baisakhi (Tyagi et al, 2012). This region is also identified as one of the most unstable (Convective Available Potential Energy, CAPE of ∼1500-3500 J⋅kg −1 ) and a suitable region to produce severe TS with intense rainfall (>7 mm⋅h −1 ) activity compared to other parts of India (Sahu et al, 2020;Sasanka et al, 2023;Tyagi et al, 2011Tyagi et al, , 2013Tyagi et al, 2012). The nonlinear nature of TS dynamics, coupled with their smaller spatial and temporal scales, makes predicting TS events a significant challenge (Osuri et al, 2017;Priya et al, 2021Priya et al, , 2022Rajeevan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During premonsoon, the eastern parts of India (Gangetic West Bengal, Assam, Odisha, Bihar, and Jharkhand) experience severe TS, locally known as Nor'westers or Kal-Baisakhi (Tyagi et al, 2012). This region is also identified as one of the most unstable (Convective Available Potential Energy, CAPE of ∼1500-3500 J⋅kg −1 ) and a suitable region to produce severe TS with intense rainfall (>7 mm⋅h −1 ) activity compared to other parts of India (Sahu et al, 2020;Sasanka et al, 2023;Tyagi et al, 2011Tyagi et al, , 2013Tyagi et al, 2012). The nonlinear nature of TS dynamics, coupled with their smaller spatial and temporal scales, makes predicting TS events a significant challenge (Osuri et al, 2017;Priya et al, 2021Priya et al, , 2022Rajeevan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…TS are a systematic natural process that transports heat, moisture, and momentum near the earth's surface to the upper level of the atmosphere to maintain the energy and moisture budget. During premonsoon, the eastern parts of India (Gangetic West Bengal, Assam, Odisha, Bihar, and Jharkhand) experience severe TS, locally known as Nor'westers or Kal-Baisakhi (Tyagi et al, 2012). This region is also identified as one of the most unstable (Convective Available Potential Energy, CAPE of ∼1500-3500 J⋅kg −1 ) and a suitable region to produce severe TS with intense rainfall (>7 mm⋅h −1 ) activity compared to other parts of India (Sahu et al, 2020;Sasanka et al, 2023;Tyagi et al, 2011Tyagi et al, , 2013Tyagi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(i) the east-west oriented region along the foothills of Himalaya and (ii) the northwest to southeast oriented region from sub-Himalayan West Bengal to Tripura. 5,6 Additionally, the monthly average of thunderstorm events is greater than 20 in Guwahati, Shillong, Imphal and Tezpur stations in April. Roy et al 7 showed that the number of thunderstorm days is highest in April and May throughout a zone spanning from the NE to West Bengal.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative step, satellite‐derived information can be used to detect thunderstorms. For example, Tyagi et al (2012) used cloud top temperature from very high‐resolution radiometer of Kalpana‐1 satellite at a spatial resolution of 8 km in 1‐h intervals to study the premonsoon thunderstorm occurrences in 2009. Previous studies have also used feature‐tracking algorithms to study mesoscale convective systems across the globe (e.g., Da Silva & Haerter, 2023; Feng et al, 2021; Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%